Allium-Derived Compound Propyl Propane Thiosulfonate (PTSO) Reduces Vibrio Populations and Increases Body Weight of European Seabass (Dicentrarchus labrax) Juveniles - Miguel Rabelo-Ruiz; Juan Manuel Peralta-Sánchez; Antonio Manuel Martín-Platero; Ana J. Ruiz; María del Mar Agraso; Laura Bermúdez; Juan José Ariza; Alberto Baños; Eva Valdivia; Manuel Martínez-Bueno (MDPI AG, 2023)
The global demand for fish products is continuously increasing as the population grows, and aquaculture plays an important role in supplying this demand. However, industrial antibiotic misuse has contributed to the spread of antimicrobial resistance among pathogenic bacteria, therefore, several antibiotic alternatives have been proposed. In this study, we have analyzed the effects of Allium-derived propyl propane thiosulfonate (PTSO) in European seabass juveniles' growth and performance. These effects were tested by measuring the body weight and analyzing the gut microbiome of fish after 89 days of feeding trial. The relative abundance of potentially pathogenic Vibrio in the foregut and hindgut of supplemented fish decreased, while Pseudomonas and Kocuria increased significantly. Alpha diversity indices significantly decreased in both gut regions of fish fed with Allium-derived PTSO supplemented diet, as well as between bacterial community composition. These results may indicate a positive effect of the supplementation in the diet with Allium-derived PTSO, reducing potentially pathogenic Vibrio and increasing body weight at the end of the experiment (89 days). However, this supplementation with Allium-derived PTSO produces changes in the diversity and composition of microbial communities, so further experiments would be necessary to explore bacterial community composition and health relationship.